2023
DOI: 10.3389/fpubh.2022.1023431
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing COVID-19, home isolation and primary health care: A mixed-methods study

Abstract: ObjectivesAlthough the vast majority of COVID-19 cases are treated in primary care, patients' experiences during home isolation have been little studied. This study aimed to explore the experiences of patients with acute COVID-19 and to identify challenges after the initial adaptation of the German health system to the pandemic (after first infection wave from February to June 2020).MethodsA mixed-method convergent design was used to gain a holistic insight into patients experience. The study consisted of a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…While psychological issues are significantly higher in individuals in centralized isolation than in those isolated at home, it does not mean that people who isolate at home will not experience psychological problems. Many studies have indicated that prolonged periods of home isolation can still lead to feelings of loneliness, anxiety, depression, and other negative emotions (46)(47)(48). Therefore, when implementing home isolation measures, it is important to consider the negative impact of home isolation and take steps to address and support people's mental wellbeing by providing resources such as psychological .…”
Section: Where To Isolate?mentioning
confidence: 99%
“…While psychological issues are significantly higher in individuals in centralized isolation than in those isolated at home, it does not mean that people who isolate at home will not experience psychological problems. Many studies have indicated that prolonged periods of home isolation can still lead to feelings of loneliness, anxiety, depression, and other negative emotions (46)(47)(48). Therefore, when implementing home isolation measures, it is important to consider the negative impact of home isolation and take steps to address and support people's mental wellbeing by providing resources such as psychological .…”
Section: Where To Isolate?mentioning
confidence: 99%
“…The patient in this study was quarantined for 10 days after the detection of SARS-CoV-2 on the first date, similar to previous a systematic review that revealed several Asian, European, and American nations with home-isolation policies ( 37 ). In addition, the medical team conducts daily follow-up calls and questionnaires to monitor patient symptoms, including the occurrence of unexpected symptoms and the impact of physical ( 38 ), mental, and emotional quarantine ( 39–41 ). Furthermore, this study was strengthened by the large number and variety of Songkhla patients who underwent HI and CI in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…We thus analyzed the qualitative telephone interviews in the sense of the new research question in addition to the survey data aiming to provide a holistic understanding of the burdening experience of HCAs during the pandemic in 2020. We compared the results of all three data sets within a triangulation protocol, using the same methodology as used in a similar study ( 22 ). We used methodological data and investigator triangulation to improve the validity of our results ( 23 ).…”
Section: Methodsmentioning
confidence: 99%